Integrating Digital Media-Based Local Wisdom to Enhance National Insight: The Role of Digital Readiness - Yoyo Zakaria Ansori; Adiwijaya Adiwijaya; Mohd Razif Idris; Mohamad Gilar Jatisunda; Dede Salim Nahdi (Journal of Innovation in Educational and Cultural Research, 2026)
This study examined the effect of local wisdom–based digital learning media on elementary students' national insight while controlling for digital readiness. A quasi-experimental matching-only pretest–posttest control group design was employed. Participants were selected through purposive sampling from one public primary school, yielding 54 Grade V students. To reduce selection bias, students were matched on pretest national insight scores, prior academic achievement, and gender distribution, yielding equivalent experimental (n = 27) and control (n = 27) groups. Data were collected using a 20-item National Insight Test (? .80) and an 18-item Digital Readiness Scale assessing technological competence, attitudes, and self-efficacy (? .80). The intervention lasted four weeks, with the experimental group receiving culturally grounded digital instruction and the control group receiving conventional instruction. Data were analyzed using Analysis of Covariance (ANCOVA), with posttest national insight as the dependent variable and digital readiness as a covariate. Assumption tests were satisfied (p .05). The overall model was statistically significant, F(2, 51) = 14.87, p .001, explaining 37% of variance in posttest scores (R² = .37). Digital readiness significantly predicted national insight, F(1, 51) = 18.42, p .001, partial ?² = .27, while instructional condition showed a smaller but significant effect, F(1, 51) = 4.36, p = .041, partial ?² = .08. The findings suggest that although culturally grounded digital media enhances national insight, students' digital readiness plays a more substantial role in determining learning outcomes.